Irrigation Scheduling as a Tool to Improve the Water Use Efficiency for Cherries Plants - Almasraf, Sabah Anwer Dawood; Al-Haddad, Amer Hassan (Nahrain University College of Engineering Journal, 2017)
Methods for scheduling irrigation are important aspects of good crop and plant management. Irrigation scheduling process is concerned with quantity and date of irrigation. In this paper Time Domain Reflectometer (TDR) is used as a soil moisture tool to measure the trend of the soil moisture in the root zone of Cherries in Michigan State/ United State of America for three years of measurements. The study analyzes the effect of irrigation process by using trickle system on the variation and trends of the soil moisture. Furthermore, the study compares the quantities of the applied water with the soil water content to get the soil water depletion and the actual crop evapotranspiration. The results show that there is no fixed and clear irrigation schedule within the years of the study (2009, 2010 and 2011). Over irrigation in some months the soil becomes in saturated conditions. On other hands, in some months and during the years of study, the soil moisture deficit be more than the allowable depletion and sometimes close to limit of permanent wilting point, and this is due to apply a deficit irrigation, knowing that the root depth of this study is 1.22 meter only, which means that the crop may be extract the water by roots that are deeper than 1.22 meter. Knowing that the saving water and energy is very important and also system evaluation and its maintenance are required.